Intravenous Tranexamic Acid Decreases Blood Transfusions and Blood Loss for Patients with Surgically Treated Hip Fractures. (20th December 2021) - Huynh, Phuong Anh N; Miller, Megan; Will, Ryan
Introduction: Tranexamic acid can decrease blood loss related to surgery and trauma. The primary objective of this study is to examine if the use of a single dose of peri-operative TXA significantly decreases the rate of allogenic blood transfusions in the setting of operative care of hip fractures. Secondary objectives included examining if total blood loss was decreased by TXA in operative hip fractures as well as examining the safety of TXA by measuring the rates venous thromboembolism (VTE). Methods: Retrospective chart review of 505 patients who were operatively treated for hip fractures at a single facility was performed. In a non-randomized fashion, 307 patients received TXA and 198 patients did not. Patients received 1 gram of TXA prior to incision. Blood transfusion was the primary end point. Blood loss was calculated using the hemoglobin balance method. Chart was reviewed for VTE events during hospitalization. Results: 505 patients were analyzed. The use of single perioperative dose of TXA in the surgical management of hip fracture resulted in absolute risk reduction of transfusion of 7.7% and relative risk reduction of transfusion by 29%. This was statistically significant with P =.04. Patients who received TXA on average lost 235 ml less blood compared to those who did not receive TXA ( P <.0001). No increase in VTE events were found in either group during hospitalization. Conclusion: This study supports the use of TXA is decrease blood loss and transfusion rates in patients with hip fractures. TXA can be used routinely to decrease complications in this usually fragile population.